Predictors of Peroneal Pathology in Broström–Gould Ankle Ligament Reconstruction for Lateral Ankle Instability. (March 2015) - Burrus, M. Tyrrell; Werner, Brian C.; Hadeed, Michael M.; Walker, Joseph B.; Perumal, Venkat; Park, Joseph S.
Background: Chronic ankle instability has a well-known association with intra- and extraarticular ankle pathologies, including peroneal tendonitis and subluxation. Patients with peroneal pathology are at risk for failure of conservative treatment for their ankle instability, thus identifying these patients is important and helps to guide management. There has been no literature looking at, in patients with chronic ankle instability, which associated ankle pathologies and patient characteristics are predictive of peroneal pathology. Methods: A retrospective chart review was performed on all patients (N = 136) who underwent a Broström–Gould ankle ligament reconstruction at a single institution from 2010 to 2014. Preoperative clinical examinations and MRIs as well as operative procedures were documented. Patients with and without peroneal pathology were divided into 2 cohorts, and their preoperative characteristics underwent a univariate analysis with P < .05 defined as showing a significant difference. Results: Of patients undergoing lateral ankle ligament reconstruction, 53.3% required operative intervention for symptomatic peroneal tendon pathology. Female gender was the only significant predictor of peroneal pathology ( P = .008). The presence of an osteochondral lesion of the talus (OLT) was a significant negative predictor of peroneal pathology ( P < .001). The remainder of the variables (age, BMI, duration of symptoms, tobacco, traumatic etiology, worker's compensation, global hyperlaxity, contralateral ankle instability, sport participation, ankle tilt, and deltoid tear) did not show a significant difference between cohorts. Conclusion: In patients who underwent Broström–Gould ankle ligament reconstruction for chronic lateral ankle instability, female gender was significantly associated with concomitant peroneal tendon pathology. Conversely, preoperative MRI findings of an OLT showed a significant negative association with peroneal pathology. All of the other variables did not show a positive or negative association. Level of Evidence: Level III, retrospective comparative case series.